Pentingnya Literasi Bahaya Hoax kepada Masyarakat Desa Sidorejo di Era Globalisasi - Intan Anggreaeni Safitri; Teddy Dyatmika (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2021)
Advances in technology have had a significant impact on human civilization today. These changes can bring people to a life that is easier and more feasible than before. One of them is in the field of information, it is easier for people to get information through various media, especially the internet. However, behind this convenience and convenience, technological advances have brought quite a crucial problem for the community. The shallow knowledge and critical attitude by the public resulted in a lot of false information or hoax news that spread widely in the community. This hoax phenomenon is not new anymore but has become a global problem, especially in Indonesia. Hoaxes or fake news generally spread faster, especially among the general public because hoaxes are packed with sensational information so that people are more motivated to spread it again. This of course has a large impact on the social life of the community. Therefore, it is necessary to have literacy or counseling to deepen knowledge and a more inclusive understanding of hoaxes so that the public becomes more aware that hoaxes are a fairly crucial problem in the social life of Indonesian people.